Pengenalan Etnomatematika Dan Etnolinguistik Banjar Melalui Siaran RRI Pro 4 Banjarmasin Kalimantan Selatan - Novia Winda; Ida Komalasari; Alimuddin A.Djdwad; Abdul Jabar; Noor Indah Wulandari; Akhmad Humaidi; Achmad Suwandi; Rizky Amaliani; Akhmad Syawaluddin (CV. Multi Kreasi Media, 2023)
Getting to know Banjar culture while learning mathematics (ethnomathematics) and getting to know Banjar culture as well as learning language (ethnolinguistics) is a new thing for people to love Banjar culture more. This service introduced ethnomathematics and ethnolinguistics to the wider community through Radio Republik Indonesia Banjarmasin. The broadcast that specifically talks about Banjar culture is the Baisukan Pandiran Event which is held every Monday at 09.00-10.00 WITA. This activity was carried out 4 times in a row regarding: a) ethnomathematics of Sultan Suriansyah Mosque, b)Ethnomathematics in Kuntau Martial Arts in South Kalimantan, c) Ethnolinguistics of Religion and Beliefs of the Banjar People, and d) Ethnolinguistics of Traditional Arts of the Banjar People.